(3fgGjI GdEjLGR aj OQGjI GdEYLGRs - (3eMeO Hf YeQ Hf GdMSf Hf GdMSjf GdJjej GdHcQj, CHh YHO Gddg, aNQ GdOjf GdQGRqj,J (B606 (3g` s; (3CHh HcQ YHO GdbGgQ Hf YHO GdQMef Hf eMeO GdLQLGfj, YHO GdbGgQ GdLQLGfj,J (B471 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdefRg Yf eTGHgg GdeMOKGJ hGdeecfGJ hHYO aEf CMb GdaVGFd HGdJbOje hdeG habfi Gddg JYGdi deWGdYI gPjf GdcJGHjf EdJbWJ efgeG eYGbO ahGFOgeG hQGYjJ GdJQJjH hSejJg fgGjI GdEjLGR ai OQGjI GdEYLGR s
(3BNQgG (B:s
(3hEfeG GdeYJHQ HGdCZQGV hGdebGUO aQHeG cGf GdeTJHg ai GddaX ZjQ ecQQ ai GdeYfi hQHeG cGf GdeJHGjf ai GddaX eJcQQkG ai GdeYfi agPG BNQ eG CQOfG EjQGOg ai gPG GdcJGH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3EfJbGAs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B48 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B310 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B606s
Keywords: (3GdHdGZIs